The earliest Serial Verb Constructions in Aramaic? Verb-verb constructions with hlk ‘go’ and ʔth ‘come’ in Old Aramaic - Locatell, Christian (Stellenbosch Papers in Linguistics Plus, 2022)
This paper presents examples in which hlk ‘walk, go’ and ʔth ‘come’ appear in multi-verb constructions conforming to the definition of asymmetrical serial verb constructions (SVCs). In these constructions, hlk and ʔth do not appear to be used with their concrete lexical senses as verbs constituting the predicate of a separate clause. Rather, they are found in the V1 position and appear to be used as minor verbs contributing an aspectual nuance of immediacy to the major verb in the V2 position. Broader usage of these verbal forms in Old Aramaic and cognate languages is consistent with a source of such SVCs from the fusion of bi-clausal constructions.